2022
DOI: 10.3897/ap.5.e0017
|View full text |Cite
|
Sign up to set email alerts
|

Study of Social and Language Skills in Children with Autism Spectrum Disorder

Abstract: One of the main obstacles to full communication and socialization is the impairment of the communication sphere in children with autism spectrum disorder. Competent diagnostics will help to identify at what level of development of social and speech skills the child is and in the future to develop goals and objectives for correctional work. This article discusses the problem of diagnosing the formation of speech and social skills in children with autism spectrum disorder, describes the results of a diagnostic s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2022
2022
2022
2022

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 5 publications
0
2
0
Order By: Relevance
“…The general stereotyped behavior and activity of people with autism are reflected in such speech phenomena as echolalia and verbal rituals (Belyaeva, 2020). Among the features of expressive speech in autism spectrum disorders, it is customary to distinguish echolalia, verbal rituals, the use of neologisms and idiosyncratic speech, the misuse of personal pronouns and verb endings (Akhmetzyanova, Artemieva & Gryaznova, 2021). These children exhibit very unusual language and communication patterns, such as stereotyped speech, and odd and ritualistic behaviors (Ibrahimagic et al, 2021).…”
Section: Employing Psycholinguistic Activities To Improve Expressive ...mentioning
confidence: 99%
“…The general stereotyped behavior and activity of people with autism are reflected in such speech phenomena as echolalia and verbal rituals (Belyaeva, 2020). Among the features of expressive speech in autism spectrum disorders, it is customary to distinguish echolalia, verbal rituals, the use of neologisms and idiosyncratic speech, the misuse of personal pronouns and verb endings (Akhmetzyanova, Artemieva & Gryaznova, 2021). These children exhibit very unusual language and communication patterns, such as stereotyped speech, and odd and ritualistic behaviors (Ibrahimagic et al, 2021).…”
Section: Employing Psycholinguistic Activities To Improve Expressive ...mentioning
confidence: 99%
“…Autism in light of these characteristics constitutes a disturbance to all those around the child, and its effects are directly reflected on the child, thus affecting his general communication, language acquisition, behavioral patterns, values and attitudes, and the method of expressing feelings and feelings (Belyaeva, 2020). In addition, the autistic child shows very few behavioral patterns compared to children who have good social acceptance, and he also suffers from abnormal socially unacceptable behavioral patterns such as social immaturity, aggression, and self-excitement (Akhmetzyanova, Artemieva & Gryaznova, 2022). Many studies have indicated that (50%) of children with ASD do not have the ability to speak, and do not develop their language skills, but they do not compensate for them by using non-verbal communication methods such as gestures or simulation, and they are unable even to use visual communication (Schmidt, 2017).…”
Section: Introductionmentioning
confidence: 99%